The BRI: A new development cooperation paradigm in the making? Unpacking China’s infrastructure cooperation along the Maritime Silk Road - Alves, Ana Cristina (2023)
This special issue aspires to contribute to the nascent literature on the developmental impact of the Belt and Road Initiative (BRI) and its implications for global development governance. It is our contention that the BRI offers a unique window for a better understanding of China’s dual role as a development agent and a development-norms shaper. This introductory essay attempts to systematize theoretical insights drawn from in-depth empirical research along key nodes of the 21st Century Maritime Silk Road (MSR), one key dimension of the BRI. This special issue provides valuable insights into BRI implementation on recipient countries by examining key infrastructure projects with the aim of uncovering the complexity of the variables determining BRI dynamics and outcomes. The contributions highlight the versatility and the fragmentation of the BRI as a cooperation platform, and the variegated nature of engagement patterns and outcomes on the ground. The findings of this collection of studies suggest that these variations are ultimately a function of the complex interaction between institutional contexts and agents from both sides (China and host countries), and that the quality and sustainability of such interplay has a significant bearing on developmental outcomes. Moreover, as with traditional donors, inconsistencies between the official rhetoric and the actual implementation dynamics and developmental outcomes may subsequently undermine China’s legitimacy as a development ‘norm-maker’ and cooperation partner. Overall, our findings question the exceptionalism of China’s development cooperation approach and hence the prospects for the emergence of an alternative and more effective development paradigm appear slim at this juncture.